Successful myomectomy using barbed sutures at 15 weeks of gestation: A case report - Yui Negoro; Michihisa Shiro; Jota Maki; Tsubasa Kokehara; Hisashi Masuyama; Shigeki Yoshida (Elsevier, 2023)
To date, there are no reports on the use of barbed sutures in myomectomy during pregnancy. Herein, successful laparotomic myomectomy at 15 weeks of gestation using barbed sutures is described. A 38-year-old pregnant woman with a large myoma (16 × 11 cm) underwent myomectomy at 15 weeks and 4 days of gestation because of strong pain at the myoma site, a high level of inflammatory markers with degeneration of uterine fibroids, and severe anemia caused by denaturation of myoma. The uterine wall was reconstructed using monofilament absorbable 0 barbed sutures. Unlike conventional sutures, barbed sutures do not retract, so an assistant does not need to hold onto it during reconstruction of the uterine wall, resulting in less pressure and damage to the gravid uterus while maintaining resistance and the ability to hold the tissue under tension. The pregnancy continued with no evidence of myometrial thinning or symptoms of preterm labor. The patient delivered a healthy baby via cesarean section due to partial placenta previa at 36 weeks. The case shows the satisfactory outcome of perinatal myomectomy using barbed sutures during pregnancy.